2022
DOI: 10.1155/2022/7684606
|View full text |Cite
|
Sign up to set email alerts
|

Significance of a Tumor Mutation Burden Gene Signature with Prognosis and Immune Feature of Gastric Cancer Patients

Abstract: Gastric cancer (GC) is a common digestive tumor which ranks the fourth most common malignancy worldwide. Immunotherapy is a promising treatment for GC, especially for advanced gastric cancer (AGC). However, in clinical practice, not all patients are sensitive to immunotherapy. Recent studies showed that tumor mutation burden (TMB) is closely correlated with the response of immunotherapy. The current study identified a TMB-related genes’ signature to predict the prognosis and immune feature of GC patients. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Although most of studies demonstrated that TMB-H GC patients could benefit from a good prognosis [12] , [13] , [14] , [15] , [16] , [17] , [18] (Table S1), there are still some studies in Chinese GC cohorts suggested TMB-H GC patients might suffer from poor prognosis [19] , [20] , [21] (Table S1). It was also reported that the TMB related genes’ signature has a predictive function in GC patients [13] , [22] , [23] . The predictive significance of TMB deserves further exploration in GC, especially in Chinese GC patients.…”
Section: Introductionmentioning
confidence: 92%
“…Although most of studies demonstrated that TMB-H GC patients could benefit from a good prognosis [12] , [13] , [14] , [15] , [16] , [17] , [18] (Table S1), there are still some studies in Chinese GC cohorts suggested TMB-H GC patients might suffer from poor prognosis [19] , [20] , [21] (Table S1). It was also reported that the TMB related genes’ signature has a predictive function in GC patients [13] , [22] , [23] . The predictive significance of TMB deserves further exploration in GC, especially in Chinese GC patients.…”
Section: Introductionmentioning
confidence: 92%